First evidence of sex-specific epidemiological differences in tattoo-like skin lesions among free-ranging bottlenose dolphins (Tursiops truncatus) - Stöfer, Luisa Christina Patricio (2024)
This thesis aims to shed light on the fascinating world of cetacean epidemiology with focus on Cetacean poxviruses and Tattoo skin disease, by giving an in-depth state of the art, and delivering a baseline data study. The skin of cetaceans is a multifaceted feature that offers a wealth of visible information. Epidermal lesions from trauma or disease are common, but the emergence, severity, and changes in demographic pattern of certain skin diseases may serve as a bioindicator for environmental change and wellbeing of a population. This study investigates tattoo-like skin lesions (TSL) in a bisexually philopatric coastal bottlenose dolphin (Tursiops truncatus) population, reporting sex-specific differences and their potential environmental implications. Data was collected in 2017 and 2018 during 145 daily boat-based surveys in Ría de Arousa-bay (NW Spain). The subsequent analysis of 10,409 photographs of 48 females and 51 males revealed an overall prevalence of 26.2%. Notably, males had a significantly higher prevalence (37.5%) compared to females (15.7%), along with increased lesion quantity in 2018. Minimum persistence time (MPT) of TSL ranged from 2.4 to 19.6 months (n=15), with males at a median of 407 days and females at 347 days. Sex-specific differences could be attributed to increased aggressive behavior and social stress but also to the very high polychlorinated biphenyl (PCB) concentrations in the area. While aggressive behavior may lead to increased cutaneous abrasions and viral entry, immunotoxic PCBs were found to be released through lactation and increased accumulation in males. Future studies should prioritize comparing populations exhibiting an equal distribution of TSL between sexes with those where males are disproportionately affected, aiming to discern differences, particularly in PCB concentration and behavioral aggression.